Estrogen Alters Remodeling of the Vaginal Wall after Surgical Injury in Guinea Pigs - Balgobin, Sunil (Society for the Study of Reproduction, Inc., 2013)
Loss of pelvic organ support (i.e., pelvic organ prolapse) is common in menopausal women. Surgical reconstruction of pelvic organ prolapse is plagued with high failure rates. The objective of this study was to determine the effects of estrogen on biomechanical properties, lysyl oxidase (LOX), collagen content, and histomorphology of the vagina with or without surgical injury. Nulliparous ovariectomized guinea pigs were treated systemically with either 50 μg/kg/day estradiol (E2,) or vehicle. After 2 wk, vaginal surgery was performed, and animals were treated with either beta-aminopropionitrile (BAPN, an irreversible LOX inhibitor), or vehicle to determine the role of LOX in recovery of the vaginal wall from injury with or without E2. Estradiol resulted in (i) significant growth, increased smooth muscle, and increased thickness of the vagina, (ii) increased distensibility without compromise of maximal force at failure, and (iii) increased total and cross-linked collagen. In the absence of E2, BAPN resulted in decreased collagen and vaginal wall strength in the area of the injury. In contrast, in E2-treated animals, increased distensibility, maximal forces, and total collagen were maintained despite BAPN. Interestingly, LOX mRNA was induced dramatically (9.5-fold) in the injured vagina with or without E2 at 4 days. By 21 days, however, LOX levels declined to near baseline in E2-deprived animals. LOX mRNA levels remained strikingly elevated (12-fold) at 21 days in the estrogenized vagina. The results suggest that prolonged E2 induced increases in LOX, and collagen cross-links may act to sustain a matrix environment that optimizes long-term surgical wound healing in the vagina.